Applying remote sensing and spatial analysis to investigateregime shifts in the Albany Thicket of the Baviaanskloof - Matowanyika, Danai (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.